The Role of History in Informality in The Global South City of Kuala Lumpur: The Case of Kampong Bharu Development - Sarayed-Din, Luiza Farnese L.; Zainol, Rosilawati; Ahmad, Faizah (Journal of Surveying, Construction and Property, 2017)
This study explores history as a critical element associated with informality in the global south city of Kuala Lumpur. Structured by such critical element and embedded in a social constructivism approach, it investigates a historical urban village under the pressure of development located in the heart of Kuala Lumpur: Kampong Bharu. Making use of secondary data review, field visit, ten semi-structured interviews and observation from June 2012 to June 2015, this study reviews the chronological urban development of Kampong Bharu. Following that, it then discusses the development of Kampong Bharu within the thematic context of modernist urban practices and single accounts of history. Highlighting how the understanding of informality is historically shaped by the same planning interventions that were supposed to remedy it, this study explores the implication of these themes on the urban crisis of global south cities, broadening the understanding of challenges and opportunities for development in Kuala Lumpur.